Automation system for Klinic Dr Rosli / Edwin Banta ... [et al.] - Banta, Edwin; Jenin, Mohd Yazid; Arshad, Mashitoh; Ramlan, Noor Liza Wati; Yusof, Rosziah (1990)
Klinik Dr. Rosli is a private clinic which operates under jurisdiction of Ministry of Health, Akta Perubatan 1971 and Malaysian Medical Association (MMA). The nature of the business entity chosen by most medical practioners varies frin sole proprietorship, partnership or through in incorporation of a company